LEARNERS’ RESPONSES ON THE EMPLOYMENT OF CULTURAL EFL MATERIAL IN ENGLISH CLASSROOMS IN PAPUA - Yohana Susana Yembise (Indonesian JELT, 2010)
The article presents research findings on the use of culturally familiar materials compared with non-culturally relevant materials. It aims at obtaining responses from highland students on the materials which are designed based on Papuan culture compared with those which are not using Papuan culture.  The study was conducted in Timika, Mimika District Papua, Indonesia, involving 80 junior high school students aged 13-15, who are from eight ethnic highlanders. The word “Papua” (used to be called Irian Jaya) in the above title is the name of the Eastern Province in Indonesia. The students involved in the classroom experimentation speak their vernacular fluently, they were considered weak in speaking Indonesian, and were low in academic performance. There were 40 students receiving culturally relevant materials, and 40 students receiving non-culturally relevant materials (conventional materials).  The data was analyzed using the Descriptive Statistical Analysis with Contingency Table Analysis to compare groups and questions.  Pearson’s chi-square statistics using SPSS was then applied to explore the significant differences in satisfaction. The results revealed that there was a significantly positive response from subjects receiving the culturally relevant materials when contrasted with those receiving the conventional materials. Keywords: Schemata; Prior knowledge, Experimental group; Conventional group; Culturally relevant material; conventional material;  EFL (English as a  Foreign Language); TEFL (Teaching English as a Foreign Language); Significance Difference in Satisfaction; Learners’ Responses